Women, music and society in Zimbabwe: perceptions and constructions - Matiure, Perminus (University of Zimbabwe Publications, 2020)
Issues of gender and sexuality have generated a lot of debate among scholars of the postmodern period. Post modernism, cosmopolitanism and feminism have all exposed and extrapolated the imbalances that exist between men and women in our societies. These gender imbalances have always been common among most of the African societies and have ultimately drawn back the endeavour by these societies to become egalitarian and homogenous. As clearly…………………………………………………………………………………………………………..